Mechanical Properties of Concrete with partial replacement of Coarse aggregates by Coconut Shells and reinforced with Coconut Fibre - Mandal Bharat; Tiwari Sushant; Ghimire Subid; Tiwari Aasish (Journal of Building Materials and Structures, 2019)
This paper centers around the study of physical and mechanical properties of concrete reinforced with coconut fibre and the coarse aggregates of which are partially replaced with coconut shells. American Concrete Institute (ACI) method has been used to design M20 concrete wherein coconut shells (CS) replaced the coarse aggregates (CA) by 6%, 8%, 10%, 12% and 14% by volume. Under each replacement of CA by CS, coconut fibres were added by 3%, 4% and 5% of cement content. Compressive strength of concrete was found to comply with characteristic strength for certain mixes which avers that the replacements were justifiable for concrete production and thus, the optimum mix for the concrete prepared thereby, would have to be considered accentuating the tensile strength which was actually the one with 10% replacement of CA by CS in terms of volume and 3% addition of coconut fibre. The research vividly evinces a decrease in overall density of the concrete thus prepared. The authors suggest the use of coconut shell and fibre in the production of concrete not only because they impart themselves as viable materials, but their use would also assist to abate the amount of environmental waste.